Equilibrium in International Trade: The United States, 1919-26 - Angell, James W. (Quarterly Journal of Economics, 1928)
I. The American balance of payments, 1919–26, 388. — Wide but strikingly parallel fluctuations of net capital and commodity movements, 390. — The domestic situation, 393. — II. General analysis of the maintenance of equilibrium in international payments, 395. — The effects of importation, 399. — The correction of excesses is not equally rapid in all cases, nor does the "causal sequence" always proceed along the same lines, 407. — III. The effects of exportation, 412. — Imports and exports taken together, 416. — The correction of excesses; effects of the business cycle. If foreign trade is relatively unimportant, the correction of large excesses must wait on domestic cyclical movements, 422. — IV. Application of these conclusions to the United States, 423. — The period 1919–21, 424. — The period 1922–26, 429. — The changes in the net items of the American balance of payments have had little effect on internal conditions; and their origin has usually made them mutually offsetting, 432.